Inferred systolic blood pressure levels to switch from lifestyle modifications to antihypertensive medications: a success-rate oriented simulation - Yoichi Ohno; Tsuneo Takenaka; Hiromichi Suzuki (Clinical and Experimental Hypertension, 2019)
Objective: This simulation study attempted to infer the systolic blood pressure (SBP) levels at which subjects with hypertension, health nurses, and primary physicians should switch their preference of their treatment policies from lifestyle modifications to antihypertensive medications in virtual Japanese sample populations. Methods: We assumed that SBP levels were normally distributed and that the incidence rate of cardiovascular disease (IRCVD, events/year) increased exponentially according to SBP. The total IRCVD was calculated by the definite integral for the product of the distribution of SBP multiplied by IRCVD at each SBP level. The success rates were calculated according to SBP and metabolic risk profiles in the two approaches, respectively. We deduced the hypothetical SBP levels by solving differential equations of ∆(IRCVD)/ ∆(SBP) = 0 using numerical analysis. Results: In the realistic situations where the subjects were not affirmative to antihypertensive medications, the inferred SBP level to switch from lifestyle modifications to antihypertensive medications should be around 150 mmHg. If the subjects are affirmative to antihypertensive medications, the SBP level should be lowered to 140 mm Hg. Conclusion: This success rate-oriented simulation proposes that the SBP level to switch from lifestyle modifications to antihypertensive medications can be modulated according to the behavioral propensity for taking antihypertensive medications. Abbreviations: The following abbreviations are used in this manuscript: CVD: cardiovascular disease; LM: lifestyle modifications; AM: antihypertensive medications; IRCVD: incidence rate of cardiovascular disease (events/year); SBP: systolic blood pressure; ∆IRCVD: the improvements in the incidence rate of cardiovascular disease by lifestyle modifications and/or by antihypertensive medications.